Diversity, Equity, and Inclusion of Dermatology Journals and Their Editorial Board Members - Julianne Kiene; Sarah Minion; Ramiro Rodriguez; Robert Dellavalle (JMIR Publications, 2023)
Dermatology as a whole suffers from minority underrepresentation. We conducted a search of the top 60 dermatology journals for mention of their approach to increasing diversity, equity, and inclusion (DEI) within their publication through editorial board members or peer-review processes. Of those 60, only 5 had DEI statements or editorial board members dedicated to increasing DEI. There are publications with checklists and frameworks for increasing DEI within the literature. We propose that more journals implement these resources within their peer-review process to increase diversity within their publication.